PSYCHOPHYSICAL TRAINING IN PHYSICAL EDUCATION OF MEDICAL STUDENTS OF SPECIAL MEDICAL GROUP - Губка, П.І. (World of Medicine and Biology, 2014)
In the article the value of psychophysical training is examined as to inalienable part of education and training of students. Attention is spared in particular, to respiratory exercises, development or support of certain level, professionally important psychical and physical qualities. Research materials allow defining influence of employments psychophysical exercises on the functional state of students of special medical group.